Limosilactobacillus fermentum MG7011: An Amylase and Phytase Producing Starter for the Preparation of Rice-Based Probiotic Beverages - Jo, Yu Mi; Kim, Ga Yun; Kim, Seul-Ah; Cheon, Seong Won; Kang, Chang-Ho; Han, Nam Soo (Frontiers in Microbiology, 2021)
The goal of this study was to develop a starter strain of Limosilactobacillus fermentum which is beneficial for human health and suitable for rice fermentation. To achieve the goal, the characteristics of 25 strains of L. fermentum were compared in terms of health promoting potentials and rice fermenting abilities. L. fermentum MG7011 was selected as a superior strain to meet the required properties. First, as probiotic traits, the strain had tolerance to gastrointestinal conditions and ability to adhere to Caco-2 and HT-29 cells. The strain showed the antioxidative activity, anti-inflammatory activity, and a protective effect on the epithelial barrier. Next, as starter traits for rice fermentation, MG7011 exhibited proper fermentation profiles in rice solution, such as fast growth rate, pH and metabolite changes, amylase and phytase activities, and optimal viscosity changes for beverage. In conclusion, L. fermentum MG7011 has excellent probiotic activities and proper starter traits in rice, thereby it can be used as a suitable probiotic starter for rice fermentation.